Thermal auxiliary material for promoting alkane dehydrogenation reaction efficiency as well as preparation method and application of thermal auxiliary material

By using thermal auxiliary materials of CuO and CaO-Al2O3 composite oxides in the alkane dehydrogenation reaction, the problem of heat generating materials being easily sintered and powdered at high temperatures is solved, and the effects of improving reaction efficiency, extending catalyst life and reducing energy consumption are achieved.

CN119709139AActive Publication Date: 2025-03-28SOUTHWEST RES & DESIGN INST OF CHEM IND

Patent Information

Application Number
CN202510239689.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-03-28
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

In the existing alkane dehydrogenation reaction, the heating material is prone to sintering and powdering under high temperature process conditions, resulting in catalyst deactivation or reduced service life, and the unstable support structure affects the overall strength and heat transfer ability of the material.

Method used

CuO is used as the main component of heating, CaO-Al2O3 composite oxide is used as the heat storage carrier, and stabilizing additives and carrier additives are added. High-strength thermal auxiliary materials are prepared through co-precipitation method, hydrothermal reaction and vacuum impregnation, which improves its structural stability and exothermic, heat storage and heat transfer capabilities.

Benefits of technology

This thermal auxiliary material has no obvious catalytic effect in the alkane dehydrogenation reaction, which can effectively improve the reaction efficiency, extend the service life of the catalyst, reduce the energy consumption of the device, and has high mechanical strength and anti-sintering properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709139A_ABST
    Figure CN119709139A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of petrochemical engineering, and particularly relates to a thermal auxiliary material for promoting alkane dehydrogenation reaction efficiency and a preparation method and application thereof. The auxiliary material is composed of a heating main body, a heat storage carrier, a stabilizing auxiliary agent and a carrier auxiliary agent. Wherein the component of the heating main body is CuO; the component of the heat storage carrier is CaO-Al2O3 composite oxide; the stabilizing auxiliary agent is one or more of Cr2O3, La2O3, CeO2 and ZrO2; and the carrier auxiliary agent is one or more of MgO, BaO, NiO and Fe2O3. The thermal auxiliary material with high mechanical strength, high heat transfer performance and high stability is synthesized through the steps of coprecipitation reaction, high-temperature hydrothermal reaction, high-temperature calcination, vacuum impregnation, ultrasonic oscillation and the like; when the material is applied to an alkane dehydrogenation olefin preparation device, alkane conversion rate and olefin selectivity can be improved, the service life of a catalyst can be prolonged, and energy consumption of the device can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and specifically relates to a thermal auxiliary material for promoting the reaction efficiency of alkane dehydrogenation (to olefins), and a preparation method and application thereof. Background Art

[0002] The technology of dehydrogenating alkanes to produce olefins was industrialized as early as the 1930s, but the route was mainly based on the steam cracking and catalytic cracking of naphtha and light fuel oil to produce olefins as by-products. It not only has high energy consumption but also low output, and can no longer meet the demand for low-carbon olefins in contemporary society. In recent years, low-carbon olefins such as ethylene, propylene, and butene have become the cornerstone of the development of the modern chemical industry. At the same time, the technology of dehydrogenating low-carbon alkanes to produce olefins, which has been booming, has become an important way to produce olefins.

[0003] Among them, ethylene, as the organic chemical raw material with the highest output in the world, is called the "mother of the petrochemical industry" and is an important organic material connecting the upstream and downstream industries of the petrochemical industry. In recent years, with the large-scale exploitation of shale gas resources in North America, the technology of producing ethylene by dehydrogenation of light ethane as a byproduct has also attracted much attention. However, at present, this emerging process or reaction process is mostly in the laboratory stage, and industrial production is relatively immature. Propylene, as one of the basic raw materials second only to ethylene in the chemical industry, is widely used in the production of polypropylene, acrylic acid, acrylonitrile, butanol, octanol, propylene oxide, isopropanol and other products. The direct dehydrogenation of propane to produce propylene has become an important way to produce propylene because of its relatively mature technology and lower comprehensive cost. Butene, as a key raw material for chemical products such as synthetic rubber, plastics, solvents, pharmaceuticals, and high-octane gasoline, has a steadily growing market demand; the direct dehydrogenation of butane to produce butene has a high maturity and low production cost, and is widely used in the petrochemical industry. In recent years, the rise of a large number of mixed alkane dehydrogenation units also represents the future development direction of alkane dehydrogenation technology.

[0004] At present, the main technologies for industrial application of low-carbon alkane dehydrogenation are the Catofin fixed bed process of Lummus Technology and the Oleflex moving bed process of UOP. Compared with the Oleflex process, the Catofin process has higher operating economy and operational adaptability due to the use of cheap chromium-based catalysts, which has gradually attracted the attention of domestic researchers. However, this process has the inherent characteristic of strong heat absorption of alkane dehydrogenation reaction in the intermittent operation mode of the fixed bed reactor, which causes the bed temperature to cool down rapidly and presents an extremely uneven temperature distribution. In recent years, the introduction of new material HGM (Heat Generation Material) in the Catofin fixed bed process has effectively improved the temperature distribution of the catalyst bed, which has a positive role in improving product yield, reducing energy consumption, improving economic benefits and reducing equipment investment.

[0005] This new type of heating material is a functional metal oxide material with oxidation and reduction properties. It has no catalytic effect on propane dehydrogenation reaction and will not cause other side reactions. This material can release a large amount of heat by reduction reaction during alkane dehydrogenation, and can also release a large amount of heat by oxidation reaction during air regeneration. Its working principle is as follows: Reduction reaction: MeO + H2(g) → Me + H2O(g) + exothermic Oxidation reaction: Me + 0.5O2(g) → MeO + exothermic Me is an active metal Generally, the heat source of the catalyst bed in the dehydrogenation reactor comes from the hot air at the top of the catalyst bed and the heat released by the injection combustion. This heating method leads to extremely uneven distribution of bed temperature and heat reserve due to uneven airflow distribution. When the area is overheated, coking will occur and the bed will be blocked; and when the area is overcooled, the catalytic efficiency will drop significantly. The heat-generating material can be selectively added to any position of the bed that requires heat. In this way, during the air regeneration stage, the material oxidizes and releases a large amount of heat, which can partially replace the heat generated by the hot air or injection combustion, reducing the energy consumption of the device; in the catalyst reduction stage, it can further release heat to increase the bed temperature; overall, the temperature compensation of the catalyst bed in this part is achieved, thereby improving the conversion rate and selectivity of propane dehydrogenation.

[0006] Chinese patent CN106029612A first disclosed an improved dehydrogenation process using heat-generating materials. The heat-generating material carriers include: aluminum oxide, aluminum hydroxide, aluminum hydroxide, boehmite, boehmite-like, gibbsite, α-alumina, aluminate, calcium aluminate, zeolite, chromium oxide, magnesium oxide, etc., and the oxides of the heat-generating component metals include: copper, chromium, molybdenum, vanadium, cerium, yttrium, etc. and their combinations, and the oxide content accounts for 2.0wt.%~40wt.% of the total weight of the heat-generating material. In particular, copper oxide is used as the heat-generating component, accounting for 3.0wt.%~20.0wt.% of the total weight of the heat-generating material. In terms of heat performance, during the reduction treatment, it increases the temperature of the propane dehydrogenation to propylene catalyst by ≥5°C, and the mixing volume ratio of the heat-generating material as an inert component to the catalyst is in the range of 3:1~1:3.

[0007] Chinese patent CN108176405B discloses an alkane dehydrogenation reaction enhancing agent, wherein the CaO content is 15wt% to 18wt%, the Al2O3 content is 70wt% to 80wt%, the CuO content is 6wt% to 15wt% and 0.01wt% to 3wt% of oxides or mixtures of elements selected from group VIII, group VI, group IA, group IIA and rare earth groups; the aluminum compound and the calcium compound are directly mixed and calcined at a high temperature of 800 to 1400°C for 0.5 to 15 hours, and then impregnated with a Cu solution.

[0008] Chinese patent CN108300430B discloses an exothermic aid for alkane dehydrogenation reaction process and its preparation method and use method. Its composition is 10-35wt% CaO, 50-85wt% Al2O3, 5-30wt% CuO, and 0-3wt% metal oxides selected from Group VIII, Group IIB, Group IIIB, and Group VIIB. Its aluminum compound, calcium compound, and solid copper compound are mixed and formed and then calcined at 800-1400℃ for 0.2-24 hours.

[0009] Chinese patent CN113388376B discloses an alkane dehydrogenation exothermic aid, its preparation method and application, which is mainly prepared from CaO, CuO and Al2O3. The Cu element in the alkane dehydrogenation exothermic aid mainly exists in the form of CaCu2O3 and Ca2CuO3, and there is no free alumina phase. It is said that the reaction of CuO and alumina to produce aluminum-copper spinel can be avoided; high-calcium calcium aluminate is used as the skeleton, and the ratio of the number of Ca atoms to the number of Al atoms is ≥6 / 7. It is said that the adhesion phenomenon caused by sintering of the carrier under certain conditions can be avoided.

[0010] Chinese patent CN117427669A discloses a method for preparing a low-carbon alkane dehydrogenation reaction auxiliary agent, which is composed of Ca, Cu, Ce, V, P, Si, and Al elements. Calculated by the mass percentage of the oxides, CaO is 5-28%, CuO is 2-22%, CeO2 is 0.8-3.3%, V2O3 is 1-4.7%, P2O5 is 0.5-2.7%, SiO2 is 5-12%, and the rest is Al2O3; Al2O3 is α-Al2O3, which is sulfur-loaded after calcination, which can passivate the pipeline and deactivate the dehydrogenator, thereby improving the dehydrogenation reaction yield.

[0011] Chinese patent CN112812752B discloses a heat storage material for catalytic dehydrogenation of propane to propylene with a specific pore structure and a preparation method thereof, wherein the heat storage material is a Cu-based material loaded with Al2O3 having a specific pore size structure. A pore-forming agent is added to modulate the pore structure and shape the Al2O3 carrier material, further improving the propane conversion rate and propylene selectivity, and releasing heat in the reduction stage and air regeneration stage, making the bed temperature distribution more uniform.

[0012] The preparation of the heat-generating / heat-releasing / heat-storing materials / auxiliaries mentioned in the above patents is basically prepared by using aluminum compounds, calcium compounds and copper compounds as the main components, and the preparation route is basically a physical mixing and calcining method. The difference is the way and type of adding the auxiliary agent. Some are to avoid the combination of the heat-generating component and the carrier, some are to increase the pore structure of the carrier, and some are to eliminate the initial activity of the dehydrogenation catalyst, etc., but none of them involve how to promote the overall structural stability of the heat-generating material, improve the mechanical strength, and improve the heat release, heat transfer, and heat absorption capacity. In the process of low-carbon alkane dehydrogenation reaction, the heat-generating material not only has to continuously absorb / release heat itself, but also has to face the circulation of high-temperature process conditions, and the cold and hot shock of gas or steam; after long-term operation, sintering and pulverization are prone to occur, resulting in the deactivation of the dehydrogenation catalyst or a reduction in service life. If the carrier structure is unstable, it is easy for the heat-releasing component to deeply combine with the carrier; if the pore structure is too rich, the overall strength of the material will be reduced; if the active components are unevenly dispersed, it will also cause the active components to accumulate and sinter, and the overall heat transfer and heat release capacity will decrease. Therefore, it is necessary to propose a method for improving the stability of the carrier structure and the heat-generating components of the heat-generating material. Summary of the invention

[0013] In view of the shortcomings of the prior art, one of the purposes of the present invention is to provide a high-strength thermal auxiliary material for improving the efficiency of alkane dehydrogenation reaction, wherein the main heat-generating component is CuO, the main heat-storing component is CaO-Al2O3 composite oxide, and a stabilizing agent and a carrier agent are added. The auxiliary material has high mechanical strength, good wear resistance, high hydrothermal stability, stable heat release, heat storage and heat transfer capabilities, has no obvious catalytic effect in the alkane dehydrogenation reaction, can effectively assist the alkane dehydrogenation catalyst, improve its conversion rate and selectivity, extend the service life of the catalyst, and reduce the energy consumption of the device.

[0014] Another object of the present invention is to provide a method for preparing the above thermal auxiliary material.

[0015] In order to achieve the above invention object, the specific technical solution of the present invention is: A thermal auxiliary material for promoting the efficiency of alkane dehydrogenation reaction, comprising a heat-generating main body, a heat storage carrier, a stabilizing auxiliary agent and a carrier auxiliary agent; wherein: the heat-generating main body component is CuO; the heat storage carrier component is a CaO-Al2O3 composite oxide; calculated as oxides, the mass percentage of each component in the auxiliary material is: 4wt.% to 15wt.% CuO, 10wt.% to 20wt.% CaO, 65wt.% to 80wt.% Al2O3, 0wt.% to 3wt.% stabilizing auxiliary agent and 0wt.% to 3wt.% carrier auxiliary agent, and the sum of the total mass percentage is 100%.

[0016] Furthermore, the carrier auxiliary agent is one or more of MgO, BaO, NiO, and Fe2O3.

[0017] Furthermore, the stabilizing agent is one or more of Cr2O3, La2O3, CeO2, and ZrO2.

[0018] As a preferred embodiment of the present invention, the method for preparing the thermal auxiliary material described above comprises the following steps: The aluminum compound, calcium compound and carrier auxiliary salt for preparing the heat storage carrier are subjected to a one-step or two-step co-precipitation reaction, and are partially or completely mixed in the form of carbonates or basic salts or basic carbonates, and then a structurally stable carrier precursor is formed through a high-temperature hydrothermal reaction, and then a densely structured heat storage carrier is formed through high-temperature calcination, and finally the heat storage carrier is loaded with heat-generating components and stabilizing additives.

[0019] More specifically, the above preparation method comprises the following specific steps: (1) First, an aluminum compound, a calcium compound, a carrier auxiliary salt and desalted water are mixed to form a mixed solution, and then an alkaline precipitant is added to perform one-step or two-step co-precipitation, and the pH value is controlled at 6.5 to 12.0 (specifically, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, etc.) to obtain a mixed precipitate; and then aging is performed; (2) After filtering, washing, beating or wet grinding the aged material in step (1), pouring it into a high-pressure hydrothermal stirring reactor, setting the stirring rate to 80-300 rpm, raising the temperature to 120-250°C, and hydrothermally reacting for 2-24 hours in a closed state, filtering the reaction material again, and drying at 80-200°C to obtain a precursor powder; (3) adding 10-20% by weight of water to the dried precursor powder in step (2) for kneading, and adding a binder for extrusion or ball forming, or adding a release agent for tableting; (4) drying and calcining the molded material in step (3); (5) impregnating the molded material calcined in step (4) with a copper salt and a stabilizing agent salt solution in a vacuum environment, and then shaking it in an ultrasonic device; (6) The sample impregnated in step (5) is dried at 100-200° C. for 2-12 h, and then calcined at 400-900° C. for 2-10 h to obtain a finished thermal auxiliary material.

[0020] Furthermore, in step (1): The aluminum compound is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum isopropoxide, basic aluminum carbonate, sodium aluminate, aluminum hydroxide, gibbsite, bayerite, norlite, boehmite, pseudoboehmite and various alumina hydrates, preferably one or more of aluminum nitrate, aluminum sulfate, aluminum chloride and aluminum isopropoxide; The calcium compound is one or more of calcium nitrate, calcium chloride, calcium bicarbonate, calcium gluconate, calcium hydrogen malate, calcium sulfate, calcium hydroxide, and calcium carbonate, preferably one or more of calcium nitrate, calcium chloride, and calcium bicarbonate; The carrier auxiliary salt is one or more of magnesium nitrate, barium nitrate, nickel nitrate, and iron nitrate, preferably magnesium nitrate; The alkaline precipitant is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, potassium carbonate and ammonia water, preferably one or two of sodium carbonate and sodium hydroxide.

[0021] The aging temperature is 60~95℃ and the time is 2~10h.

[0022] Furthermore, in step (2): The washing step is usually performed with hot water at room temperature to 80°C, and the number of washing times is 2 to 4 times; The beating or wet grinding step generally uses a beating machine or a wet ball mill to further evenly mix the washed materials, and the mixing time is 1 to 3 hours.

[0023] Furthermore, in step (3): The binder is one or more of carboxymethyl cellulose, field pine powder, polyvinyl alcohol, aluminum sol, and pseudo-boehmite; The amount of the binder added is 0-2% by weight of the precursor powder, preferably 0-0.5%; The release agent is one or more of graphite, magnesium stearate, aluminum stearate, and calcium stearate, preferably calcium stearate; The addition amount of the release agent is 0-1% by weight of the precursor powder, preferably 0-0.5%.

[0024] Furthermore, in step (4): The drying temperature is 60-200°C, preferably 75-80°C; the drying time is 4-24h, preferably 10-12h; The calcination temperature is 1000-1600° C., preferably 1200-1500° C.; the calcination time is 2-12 hours, preferably 4-6 hours.

[0025] Furthermore, in step (5): The copper salt is one or more of copper nitrate, copper sulfate, and copper chloride, preferably copper nitrate; The copper salt concentration is 3-9 mol / L, preferably 4-6 mol / L; The impregnation method is one of excessive impregnation, spray impregnation, and equal volume impregnation under vacuum conditions, preferably excessive impregnation; the impregnation temperature is preferably 50-80°C; The vacuum degree is -50~-100kPa, preferably -70~-90kPa; The stabilizing agent is one or more of chromium nitrate, lanthanum nitrate, cerium nitrate, zirconium nitrate and bismuth nitrate.

[0026] The thermal auxiliary material prepared by any of the above methods has a specific surface area of ​​0.5 to 20 m 2 / g, mercury intrusion pore volume is 0.1-0.35ml / g, apparent density is 1.5-2.5g / ml, radial lateral compression strength is ≥400N / cm.

[0027] The third object of the present invention is to provide an application of a thermal auxiliary material in alkane dehydrogenation reaction.

[0028] Furthermore, the thermal auxiliary material described above is used in the reaction of dehydrogenating alkanes to olefins.

[0029] Furthermore, the thermal auxiliary material described above is used in the direct dehydrogenation of C2~C5 alkanes to produce light olefins, and is physically mixed with an alkane dehydrogenation catalyst for use.

[0030] Furthermore, in the above-mentioned application, the alkane dehydrogenation temperature is 380~900℃, the pressure is -0.07~2.0Mpa(g), and the alkane mass space velocity is 0.3~5h -1 ; The mass mixing ratio of the catalyst and the thermal auxiliary material is 0.5~10:1.

[0031] Further, the preferred alkane dehydrogenation application conditions are as follows: The alkane raw material is preferably propane, and the propane dehydrogenation catalyst and the thermal auxiliary material are mixed in a mass ratio of (0.5~10):1. The reaction form is preferably a fixed bed batch reaction, the operating temperature is preferably 450~650℃, the pressure is preferably -0.06~-0.04Mpa(g), and the propane mass space velocity is preferably 0.5~2h -1 The operation cycle is 20~40min, which includes dehydrogenation reaction, steam purge, air regeneration, hydrogen reduction, nitrogen replacement and other steps.

[0032] Compared with the prior art, the positive effects of the present invention are embodied in: (1) The co-precipitation method is used to precipitate or partially precipitate the support components, which can effectively improve the mixing degree of Al compounds and Ca compounds at the molecular level, providing favorable conditions for the formation of the support precursor in the next step; (2) The carrier precipitate is conducive to the formation of a crystal-shaped and structurally stable calcium aluminum compound precursor through a high-temperature hydrothermal reaction, and then after high-temperature calcination, a CaO-Al2O3 composite oxide with a dense structure and excellent heat storage performance can be formed; (3) By adding carrier additives, the sintering temperature of the carrier is effectively reduced, while the shrinkage rate of the carrier is increased, the discharge of micro-pores in the carrier is promoted, the density and strength of the material are improved, and the production energy consumption is reduced; (4) Active copper metal can be loaded by impregnation under vacuum conditions and ultrasonic vibration, which can effectively improve its impregnation depth and uniformity in the carrier, and effectively improve the anti-sintering ability of the copper component during high-temperature operation through the spatial confinement effect of the stabilizing additive.

[0033] (5) The present invention synthesizes a thermal auxiliary material with high mechanical strength, sintering resistance, high heat transfer and high stability through the steps of co-precipitation reaction, high temperature hydrothermal reaction, high temperature calcination, vacuum impregnation and ultrasonic vibration; when the material is used in an alkane dehydrogenation device, it is beneficial to improve the alkane conversion rate and olefin selectivity, extend the catalyst operating life, and reduce the energy consumption of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of a propane dehydrogenation evaluation device; Figure 2 This is a propane dehydrogenation cycle operation diagram (excerpt) of Example 9; Figure 3 This is the propane dehydrogenation cycle operation diagram of Comparative Example 3 (excerpt). DETAILED DESCRIPTION

[0035] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0036] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other alternative features that are equivalent or have similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0037] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0038] In this application, unmarked % indicates mass percentage.

[0039] In the present invention, some conventional operating equipment, devices and components are omitted or only briefly described.

[0040] Embodiment 1: The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 75%, CaO: 15%, CuO: 9.5%, carrier auxiliary agent: 0.5%, and stabilizing auxiliary agent: 0%.

[0041] The preparation method of the thermal auxiliary material is: S1: Weigh 551.9g aluminum nitrate nonahydrate, 63.0g calcium nitrate tetrahydrate, 3.2g magnesium nitrate hexahydrate and mix them evenly with an appropriate amount of water to prepare a mixed salt solution, and then drip them into a constant temperature reactor in parallel with the prepared excess sodium carbonate alkali solution, control the pH to 8.0, maintain the temperature of the reactor at 75°C, and age for 3h; obtain a carrier precipitate; S2: The aged precipitated material was filtered and washed with 50°C hot water for 3 times, poured into a pulper and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 150 rpm, and the hydrothermal reaction was carried out at 200°C for 2 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; S3: The dried precursor powder is added with 15% water and 0.5% pseudo-boehmite by weight, kneaded thoroughly, and then extruded into a strip shape through a die with a pore size of 4.0 mm.

[0042] S4: After drying the molded material at 80°C for 12 hours, place it in a high-temperature muffle furnace and calcine it at 1300°C for 4 hours; S5: Weigh 250g of copper nitrate trihydrate and appropriate amount of water to prepare an excess impregnation solution with a concentration of 5.5mol / L, and pour it into a separatory funnel; take another 50.0g of the calcined extruded strip sample and put it into a dry suction filtration bottle, and evacuate it to -90kpa in a constant temperature water bath at 50℃, then use a separatory funnel to slowly add the impregnation solution into the suction filtration bottle to submerge the surface of the carrier, and perform vacuum impregnation for 0.5h; then, ultrasonically impregnate it in an ultrasonic oscillator at normal pressure for 0.5h; S6: The impregnated sample was dried at 100°C for 10 hours and then calcined at 650°C for 4 hours to obtain a finished thermal auxiliary material.

[0043] Example 2 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 70%, CaO: 20%, CuO: 9%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 0%.

[0044] The preparation method of the thermal auxiliary material is: S1: Weigh 153.7g of calcium gluconate, 1.7g of barium nitrate and an appropriate amount of water and mix them evenly to prepare a mixed solution. Weigh 141.8g of sodium aluminate and an appropriate amount of water to prepare a sodium aluminate solution. The two streams of materials are dripped into a constant temperature reactor in parallel, and the pH is adjusted with sodium carbonate lye to control the pH to 10. Keep the temperature of the reactor at 80°C and age for 3h; S2: The aged precipitate material was filtered and washed with 50°C hot water for 3 times, poured into a ball mill for wet ball milling for 2 hours, and then poured into a high-pressure hydrothermal stirring reactor, with the stirring rate set at 150 rpm, and hydrothermally reacted at 250°C for 4 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; S3: 11% by weight of water and 0.8% of sesbania powder were slowly added to the dried precursor powder and kneaded, and then extruded through a die with a pore size of 4.0 mm to form a strip.

[0045] S4: drying the molded material at 60°C for 12h, and then calcining at 1500°C for 2h; S5: Weigh 250g of copper nitrate trihydrate and an appropriate amount of water to prepare an excess impregnation solution with a concentration of 5.8mol / L, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 1h; S6: The impregnated sample was dried at 110°C for 10 h and then calcined at 500°C for 4 h to obtain a finished thermal auxiliary material.

[0046] Example 3 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 72%, CaO: 20%, CuO: 7%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 0%.

[0047] The preparation method of the thermal auxiliary material is: Step 1: Weigh 144.2g of aluminum isopropoxide, 38.7g of calcium chloride, and 3.9g of nickel nitrate hexahydrate and mix them evenly with an appropriate amount of water to prepare a mixed salt solution, and drip them into a constant temperature reactor in parallel with the prepared excess sodium hydroxide lye, control the pH to 8.5, maintain the temperature of the reactor at 75°C, and age for 3h; Step 2: The aged material was filtered and washed with 50°C hot water for 3 times, poured into a pulper and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 150 rpm, the temperature was raised to 180°C, and the hydrothermal reaction was performed for 8 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: 15% by weight of water and 0.5% by weight of carboxymethyl cellulose are added to the dried precursor powder and kneaded, and then extruded through a die with a pore size of 4.0 mm to form a strip.

[0048] Step 4: Dry the molded material at 90°C for 12 hours and then calcine at 1400°C for 2 hours; Step 5: Weigh 250g of copper nitrate trihydrate and appropriate amount of water to prepare an excess impregnation solution with a concentration of 5.0mol / L, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 1h; Step 6: The impregnated sample was dried at 110°C for 10 h and then calcined at 700°C for 6 h to obtain the finished product.

[0049] Example 4 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 73%, CaO: 20%, CuO: 6.8%, carrier auxiliary agent: 0.2%, and stabilizing auxiliary agent 0%.

[0050] The preparation method of the thermal auxiliary material is: Step 1: Weigh 544.4g aluminum nitrate nonahydrate, 63.2g calcium nitrate tetrahydrate, 1.0g ferric nitrate nonahydrate and mix them evenly with appropriate amount of water to prepare a mixed salt solution, and then drip them into a constant temperature reactor with the prepared excess sodium hydroxide solution, control the pH to 9.0, maintain the temperature of the reactor at 80°C, and age for 3h; Step 2: The aged material was filtered and washed twice with 50°C hot water, mixed in a beater for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, with a stirring rate of 150 rpm, 200°C, and a hydrothermal reaction of 10 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: Add 15% by weight of water and 0.5% by weight of aluminum stearate to the dried precursor powder for granulation, and then press into tablets.

[0051] Step 4: Dry the molded material at 100°C for 12 hours and then calcine at 1400°C for 2 hours; Step 5: Weigh 250g of copper nitrate trihydrate and appropriate amount of water to prepare an excess impregnation solution with a concentration of 4.5mol / L, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 1h; Step 6: The impregnated sample was dried at 100°C for 10 hours and then calcined at 600°C for 4 hours to obtain the finished product.

[0052] Example 5 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 72%, CaO: 20%, CuO: 6.5%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 0.5%.

[0053] The preparation method of the thermal auxiliary material is: Step 1: Weigh 529.4g aluminum nitrate nonahydrate, 70.0g calcium nitrate tetrahydrate, 6.4g magnesium nitrate hexahydrate and mix them evenly with appropriate amount of water to prepare a mixed salt solution, and then add them to the prepared excess potassium hydroxide alkali solution and drip them into a constant temperature reactor, control the pH to 8.0, maintain the temperature of the reactor at 80°C, and age for 3h; Step 2: The aged material was filtered and washed twice with 50°C hot water, mixed in a beater for 2 hours, and then poured into a high-pressure hydrothermal stirring reactor, with the stirring rate set at 150 rpm, and hydrothermally reacted at 220°C for 4 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: adding 12% by weight of water and 0.5% of pseudo-boehmite to the dried precursor powder for kneading, and then extruding through a die with a hole diameter of 4.0 mm to form a strip; Step 4: Dry the molded material at 80°C for 12 hours and then calcine at 1300°C for 4 hours; Step 5: Weigh 250g of copper nitrate trihydrate and 33.6g of chromium nitrate nonahydrate, add appropriate amount of water to prepare an excess impregnation mixed solution, then add 50.0g of the calcined extruded sample, evacuate to -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 1h; Step 6: The impregnated sample was dried at 110°C for 12 hours and then calcined at 500°C for 4 hours to obtain the finished product.

[0054] Example 6 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 75%, CaO: 15%, CuO: 8%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 1.0%.

[0055] The preparation method of the thermal auxiliary material is: Step 1: Weigh 551.9g aluminum nitrate nonahydrate, 63.2g calcium nitrate tetrahydrate, 6.4g magnesium nitrate hexahydrate and mix them evenly with an appropriate amount of water to prepare a mixed salt solution, and then drip them into a constant temperature reactor in parallel with the prepared excess sodium carbonate alkali solution, control the pH to 8.5, maintain the temperature of the reactor at 75°C, and age for 3h; Step 2: The aged material was filtered and washed with 50°C hot water for 3 times, put into a beater and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 150 rpm, and the hydrothermal reaction was carried out at 200°C for 12 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: Add 20% water and 0.5% Tianqing powder to the dried precursor powder and knead it, then extrude it into strips through a die with a pore size of 4.0 mm.

[0056] Step 4: Dry the molded material at 110°C for 12 hours and then calcine at 1300°C for 4 hours; Step 5: Weigh 250g of copper nitrate trihydrate and 36.67g of lanthanum nitrate hexahydrate, add appropriate amount of water to prepare an excess impregnation mixed solution, then add 50.0g of the calcined extruded sample, evacuate to -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 0.5h; Step 6: The impregnated sample was dried at 120°C for 10 h and then calcined at 450°C for 6 h to obtain the finished product.

[0057] Example 7 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 75%, CaO: 17%, CuO: 6%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 1.0%.

[0058] The preparation method of the thermal auxiliary material is: Step 1: Weigh 551.9g aluminum nitrate nonahydrate, 71.6g calcium nitrate tetrahydrate, 1.7g barium nitrate and an appropriate amount of water, mix them evenly to form a mixed salt solution, and then drip them into a constant temperature reactor in parallel with the prepared excess sodium hydroxide alkali solution, control the pH at the end point to 9.0, maintain the temperature of the reactor at 80°C, and age for 3h; Step 2: The aged material was filtered and washed with 50°C hot water for 3 times, then put into a beater and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 150 rpm, and the hydrothermal reaction was carried out at 230°C for 5 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: Slowly add 15% by weight of water and 1% of aluminum sol to the dried precursor powder for kneading, and then extrude it into strips through a die with a pore size of 4.0 mm.

[0059] Step 4: Dry the molded material at 100°C for 12 hours and then calcine at 1200°C for 8 hours; Step 5: Weigh 250.0g of copper nitrate trihydrate and 34.8g of cerium nitrate and add appropriate amount of water to prepare an excess impregnation mixed solution, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 0.5h; Step 6: The impregnated sample was dried at 100°C for 10 hours and then calcined at 580°C for 4 hours to obtain the finished product.

[0060] Example 8 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 73%, CaO: 20%, CuO: 6%, carrier auxiliary agent: 0%, and stabilizing auxiliary agent: 1.0%.

[0061] The preparation method of the thermal auxiliary material is: Step 1: Weigh 295.3g of aluminum isopropoxide, 84.3g of calcium nitrate tetrahydrate and an appropriate amount of water, mix them evenly to prepare a mixed salt solution, and drip them into a constant temperature reactor in parallel with the prepared excess sodium carbonate alkali solution, control the pH to 8.5, maintain the temperature of the reactor at 75°C, and age for 3h; Step 2: The aged material was filtered and washed twice with 50°C hot water, then put into a beater and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 200 rpm, and the hydrothermal reaction was carried out at 230°C for 5 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: Slowly add 17% by weight of water and 0.5% of sesbania powder to the dried precursor powder and knead it, then extrude it into strips through a die with a pore size of 4.0 mm.

[0062] Step 4: Dry the molded material at 100°C for 12 hours and then calcine at 1450°C for 2 hours; Step 5: Weigh 250.0g of copper nitrate trihydrate and 48.1g of zirconium nitrate pentahydrate and add appropriate amount of water to prepare an excess impregnation mixed solution, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 0.5h; Step 6: The impregnated sample was dried at 100°C for 10 hours and then calcined at 700°C for 6 hours to obtain the finished product.

[0063] Example 9 The components of the thermal auxiliary material in this embodiment are as follows by mass percentage: Al2O3: 75%, CaO: 15%, CuO: 8.7%, carrier auxiliary agent: 1.0%, and stabilizing auxiliary agent: 0.3%.

[0064] The preparation method of the thermal auxiliary material is: Step 1: Weigh 551.9g aluminum nitrate nonahydrate, 63.2g calcium nitrate tetrahydrate, 6.4g magnesium nitrate hexahydrate and mix them evenly with appropriate amount of water to prepare a mixed salt solution, and drip them into a constant temperature reactor in parallel with the prepared excess sodium carbonate alkali solution, control the pH to 8.5, maintain the temperature of the reactor at 75°C, and age for 3h; Step 2: The aged material was filtered and washed with 50°C hot water for 3 times, then put into a beater and mixed for 1 hour, and then poured into a high-pressure hydrothermal stirring reactor, the stirring rate was set to 100 rpm, and the hydrothermal reaction was carried out at 250°C for 4 hours. After completion, the material was filtered and dried at 110°C to obtain a precursor powder; Step 3: Add 15% water and 0.2% Tianqing powder to the dried precursor and knead it, then extrude it into strips through a die with a pore size of 4.0 mm.

[0065] Step 4: Dry the molded material at 80°C for 12 hours and then calcine at 1340°C for 4 hours; Step 5: Weigh 250.0g of copper nitrate trihydrate and 15.0g of chromium nitrate nonahydrate, add appropriate amount of water to prepare an excess impregnation mixed solution, then add 50.0g of the calcined extruded sample, evacuate to a vacuum of -90kpa, and perform vacuum impregnation in a constant temperature water bath at 50°C for 0.5h; then immerse in an ultrasonic oscillator at normal pressure for 1h; Step 6: The impregnated sample was dried at 110°C for 12 hours and then calcined at 680°C for 4 hours to obtain the finished product.

[0066] Comparative Example 1 The component mass percentages of the thermal auxiliary material in this comparative example are: Al2O3: 77%, CaO: 15%, CuO: 8%; what is different from the embodiment is that the common solid mixing method is used to prepare the carrier, and no auxiliary agent is added.

[0067] The specific preparation process is as follows: Step 1: 120g of pseudo-boehmite and 20.0g of calcium hydroxide were physically mixed in a ball mill for 5h, and after the mixing was completed, 30.0mL of water and 1% aluminum sol were slowly added dropwise for kneading, and finally extruded into strips; Step 2: After drying the molded material in the first step at 100°C for 12 hours, the dried material is calcined at 1400°C for 4 hours; Step 3: Weigh 250g of copper nitrate trihydrate according to its water absorption rate and add appropriate amount of water to prepare excess impregnation solution, then add 50g of calcined extruded sample for room temperature impregnation; Step 4: The impregnated sample was dried at 100°C for 10 hours and then calcined at 600°C for 4 hours to obtain a comparative example finished product.

[0068] Comparative Example 2 The component mass percentage and preparation method of the thermal auxiliary material in this comparative example are the same as those in Example 9, with the only difference being that the aged material obtained in the S1 process is directly dried at 110° C. without executing the S2 step, and the comparative example finished product is obtained through the S3 to S6 preparation steps.

[0069] Comparative Example 3 A sample of commercial heating material used in a domestic propane dehydrogenation to propylene industrial unit.

[0070] test: The finished products / samples obtained in the above examples and comparative examples were respectively characterized in terms of physical and chemical properties and evaluated on a propane dehydrogenation evaluation device.

[0071] 1. Characterization of physical and chemical properties This section selects the finished products of the heating materials prepared in the above embodiments and comparative examples for characterization of physical and chemical properties, mainly analyzing the nitrogen adsorption specific surface area, mercury intrusion pore volume, bulk density, and radial lateral compressive strength of each sample.

[0072] The analytical instruments used: the nitrogen adsorption analyzer uses the American Micromeritics ASAP 2460 nitrogen adsorption analyzer; the mercury intrusion analyzer uses the American Micromeritics AutoPore IV 9500 2.03.01 mercury intrusion analyzer; the apparent density and radial lateral compressive strength determination methods refer to the industry standards well known in the industry. The specific determination results are summarized in Table 1.

[0073] Table 1 Summary of physical and chemical properties of finished products in the embodiments and comparative examples

[0074] As can be seen from Table 1, the specific surface area of ​​the thermal auxiliary material of Examples 1 to 9 using the preparation method described in the present invention is 1 to 6 m 2 / g, mercury intrusion pore volume of 0.1-0.35ml / g, apparent density of 1.6-2.5g / ml, radial side compression strength ≥400N / cm. Compared with comparative examples 1-2, it has higher mechanical strength. This may be because the coprecipitation method and hydrothermal synthesis greatly promote the mutual combination of calcium and aluminum to form dense calcium aluminum spinel, but with the type, content, hydrothermal temperature and calcination temperature of the carrier additive, the apparent density of the formed material also changes. In particular, the thermal auxiliary materials prepared in Examples 5, 6 and 9 not only have better mechanical strength than the sample in Comparative Example 3, but also their specific surface area, pore volume and apparent density are similar to those of Comparative Example 3.

[0075] 2. Propane dehydrogenation performance evaluation test The promoting effect of Examples 1 to 9 and the comparative example on the propane dehydrogenation to propylene reaction was evaluated in a fixed bed batch reactor. The specific device schematic is shown in the attached Figure 1 shown.

[0076] In each propane dehydrogenation test, 25 g of the thermal auxiliary material of each embodiment and comparative example was uniformly mixed with 35 g of the same commercial chromium-based propane dehydrogenation catalyst and loaded into a high-temperature reaction tube with a ceramic lining of Φ40 mm; the operating temperature was set to 580 ° C, the reaction pressure was -0.05 MPa (g), and the propane mass space velocity was 0.9 h-1 The operation cycle was 30 minutes, including 600 seconds of dehydrogenation reaction, 150 seconds of nitrogen purge, 100 seconds of steam purge, 640 seconds of air regeneration, 150 seconds of nitrogen replacement, and 160 seconds of hydrogen reduction. Each sample was cycled 50 times continuously, and a comprehensive sample of the outlet gas was taken each time and analyzed on an Agilent 8860 gas chromatograph. The analysis results of 5 and 50 times for each sample are listed in Table 2.

[0077] Table 2 Conversion rate and selectivity of propane dehydrogenation in which the finished products of thermal auxiliary materials of the embodiments and comparative examples are involved

[0078] The blank sample is a dehydrogenation reaction process in which the thermal auxiliary material is replaced by inert Al2O3 particles; the partial cycle operation diagram and single operation diagram of Example 9 are shown in the attached Figure 2 ; Partial cycle operation diagram and single operation diagram of comparative example 3 are attached Figure 3 .

[0079] Table 3 Comparison of copper grain size before and after use of the embodiment and the comparative example

[0080] It can be seen from Table 2 that Examples 1-9 have higher propane conversion rates and propylene selectivities than Comparative Example 1 and the blank example; in particular, Example 9 has better conversion rate and selectivity, which is due to its stable carrier structure and stable heat release efficiency, while the blank sample without any thermal auxiliary material is quickly deactivated by carbon deposition due to too low regeneration temperature; in addition, compared with Comparative Example 2, Example 9 is mainly reflected in the dense structure of the carrier, which can ensure that it can stably promote the propane dehydrogenation reaction in the cyclic reaction without large performance fluctuations. Secondly, the stable carrier is also conducive to the impregnation of the heat-generating component, and the expansion and collapse of the carrier after impregnation will not occur; Compared with Comparative Example 3, Example 9 is combined with the attached Figure 2 and attached Figure 3 It can be seen that the operation spectra of the thermal auxiliary material prepared by the present invention and the commercial heating material are very similar, but due to the better heat release performance, the promoting effect on the propane dehydrogenation catalyst is significantly better than that of the commercial heating material, which reflects the usefulness and innovation of the patent of the present invention.

[0081] The data in Table 3 further illustrate that the thermal auxiliary materials prepared in Examples 5, 6, 7, 8, and 9 using stabilizing agents have better copper dispersibility and smaller particle size. After 50 cycles, the copper grains are basically unchanged or the copper grains become smaller. However, in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 without adding stabilizing agents, the copper grains are obviously enlarged. Therefore, the addition of stabilizing agents is beneficial to maintaining the stability of the active components during high temperature operation.

[0082] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

[0083] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.

Claims

1. A thermal auxiliary material for promoting the efficiency of alkane dehydrogenation reaction, characterized in that: The auxiliary material comprises a heating body, a heat storage carrier, a stabilizing agent and a carrier agent; wherein: the heating body component is CuO; the heat storage carrier component is a CaO-Al2O3 composite oxide; the stabilizing agent is one or more of Cr2O3, La2O3, CeO2, and ZrO2; the carrier agent is one or more of MgO, BaO, NiO, and Fe2O3; calculated as oxides, the mass percentage of each component in the auxiliary material is: 4wt.% to 15wt.% CuO, 10wt.% to 20wt.% CaO, 65wt.% to 80wt.% Al2O3, 0wt.% to 3wt.% stabilizing agent and 0wt.% to 3wt.% carrier agent, and the sum of the total mass percentage is 100%; The preparation method of the thermal auxiliary material comprises the following steps: the aluminum compound, calcium compound and carrier auxiliary salt for preparing the heat storage carrier are subjected to a one-step or two-step co-precipitation reaction, and part or all of them are evenly mixed in the form of carbonate, basic salt or basic carbonate complex salt, and then a structurally stable carrier precursor is formed by a high-temperature hydrothermal reaction, and then a densely structured heat storage carrier is formed by high-temperature calcination, and finally a heat-generating component and a stabilizing auxiliary agent are loaded on the heat storage carrier to obtain the product.

2. The method for preparing the thermal auxiliary material according to claim 1, characterized in that The specific steps are as follows: (1) First, an aluminum compound, a calcium compound, a carrier auxiliary salt and desalted water are mixed to form a mixed solution, and then an alkaline precipitant is added, and a one-step or two-step co-precipitation is performed to control the pH value to be 6.5-12.0 to obtain a mixed precipitate; and aging is performed; (2) After filtering, washing, beating or wet grinding the aged material in step (1), pour it into a high-pressure hydrothermal stirring reactor, set the stirring rate to 80-300 rpm, raise the temperature to 120-250°C, and perform hydrothermal reaction in a closed state for 2-24 hours, filter the reaction material again, and dry it at 80-200°C to obtain a precursor powder; (3) adding 10-20% by weight of water to the dried precursor powder in step (2) for kneading, and adding a binder for extrusion or ball forming, or adding a release agent for tableting; (4) drying and calcining the molded material in step (3); (5) impregnating the molded material calcined in step (4) with a copper salt and a stabilizing agent salt solution in a vacuum environment, and then shaking it in an ultrasonic device; (6) The sample impregnated in step (5) is dried at 100-200° C. for 2-12 h, and then calcined at 400-900° C. for 2-10 h to obtain a finished thermal auxiliary material.

3. The method for preparing the thermal auxiliary material according to claim 2, characterized in that: In step (1), The aluminum compound is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum isopropoxide, basic aluminum carbonate, sodium aluminate, aluminum hydroxide, gibbsite, bayerite, norlite, boehmite, and pseudo-boehmite; The calcium compound is one or more of calcium nitrate, calcium chloride, calcium bicarbonate, calcium gluconate, calcium hydrogen malate, calcium sulfate, calcium hydroxide, and calcium carbonate; The carrier auxiliary salt is one or more of magnesium nitrate, barium nitrate, nickel nitrate and iron nitrate; The alkaline precipitant is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, potassium carbonate and ammonia water; The aging temperature is 60~95℃, and the time is 2~10h.

4. The method for preparing the thermal auxiliary material according to claim 2, characterized in that: In step (2), The washing step uses hot water at room temperature to 80°C for 2 to 4 times; In the beating or wet grinding step, a beating machine or a wet ball mill is used to further evenly mix the washed materials, and the mixing time is 1 to 3 hours.

5. The method for preparing the thermal assist material according to claim 2, characterized in that: In step (3), The binder is one or more of carboxymethyl cellulose, field pine powder, polyvinyl alcohol, aluminum sol, and pseudo-boehmite; The amount of the binder added is 0-2% of the weight of the precursor powder; The release agent is one or more of graphite, magnesium stearate, aluminum stearate, and calcium stearate; The added amount of the release agent is 0-1% of the weight of the precursor powder.

6. The method for preparing the thermal assist material according to claim 2, characterized in that: In step (4), The drying temperature is 60-200°C and the drying time is 4-24h; The calcination temperature is 1000-1600°C, and the calcination time is 2-12h.

7. The method for preparing the thermal assist material according to claim 2, characterized in that: In step (5), The copper salt is one or more of copper nitrate, copper sulfate and copper chloride; The copper salt concentration is 3-9 mol / L; The impregnation method is one of excessive impregnation, spray impregnation, and equal volume impregnation under vacuum conditions; the impregnation temperature is 50-80° C., the impregnation time is 0.5-2 hours; and the impregnation is performed in an ultrasonic device for 0.5-2 hours; The vacuum degree is -50~-100kpa; The stabilizing agent is one or more of chromium nitrate, lanthanum nitrate, cerium nitrate and zirconium nitrate.

8. Use of the thermal auxiliary material according to claim 1 or the thermal auxiliary material prepared by the method according to any one of claims 2 to 7 in the dehydrogenation of alkanes to olefins.

9. The use according to claim 8, characterized in that It is used in the direct dehydrogenation of C2~C5 alkanes to produce low-carbon olefins, and is physically mixed with an alkane dehydrogenation catalyst; the alkane dehydrogenation temperature is 380~900℃, the pressure is -0.07~2.0Mpa(g), and the alkane mass space velocity is 0.3~5h -1 ; The mass mixing ratio of the catalyst and the thermal auxiliary material is 0.5~10:1.

Citation Information

Patent Citations

  • Alkane dehydrogenating exothermic auxiliary agent as well as preparation method and using method thereof

    CN108300430A

  • Preparation method of light alkane dehydrogenation reaction aid

    CN117427669A

  • Heat balance material used in light alkane dehydrogenation process as well as preparation method and application of heat balance material

    CN117925196A

  • Heat balance auxiliary agent for preparing propylene through propane dehydrogenation and preparation method of heat balance auxiliary agent

    CN118751248A

  • Low-carbon alkane chromium dehydrogenation catalyst, preparation method therefor and application thereof

    WO2024008168A1

Cited By

  • Heat storage material as well as preparation method and application thereof

    CN121495546A

  • Heat balance aid for propane dehydrogenation reaction as well as preparation method and application of heat balance aid

    CN122399838A